Characterization of seeds from a tropical evergreen forest of western Cuba. Ecological correlations among traits - Montejo Valdés, Laura A; Sánchez, Jorge A; Muñoz, Bárbara C; Gamboa, Alejandro (Bosque (Valdivia), 2017)
Seed traits are determined in 50 species from an evergreen forest in Sierra del Rosario, Cuba. These traits were analyzed at their community level, according to life form and season dispersal/collection. For this, we also included 40 trees species previously studied on the place. The variables studied were: number of seeds per fruit, seed mass (fresh/dry), coat dry mass, percentage of biomass allocation to the physical defenses (testa/endocarp) and water content. We found that trees exhibited the widest range in the number of seeds per fruit, seed mass and water content. It was also confirmed that life form significantly affected the variables of seminal mass, while there were no significant differences in the variables assessed when species were grouped according to their season dispersal. Nevertheless, seeds with larger total mass, coat dry mass and less hydration were collected during the dry season. At community level, in trees, shrubs and in rain (early/later) a negative correlation between seeds per fruit and the variables of mass was found. In the beginning of the rainy season, humidity content was positively correlated with total mass, and negatively correlated with the number of seeds and the percentage of coat, across all the 90 species and in trees. These results corroborate the presence of high variability in seed traits in the functional groups studied, and also in the correlations established among them. Nevertheless, in general, the seeds presenting bigger size and higher humidity were less numerous and showed thin coats.